Forage Soybeans for Grazing, Hay and Silage - Ann R. Blount; David L. Wright; Richard K. Sprenkel; Tim D. Hewitt; Clif K. Hiebsch; Bob O. Myer (EDIS)
Livestock producers need a high-protein summer forage. Forage soybeans fit well in a production system following small grains or early planted corn. This document is SS-AGR-180, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Revised January 2003.